2018
DOI: 10.3390/ijms19020560
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of N-Terminal Domain Removal towards the Biochemical and Structural Features of a Thermotolerant Lipase from an Antarctic Pseudomonas sp. Strain AMS3

Abstract: Lipase plays an important role in industrial and biotechnological applications. Lipases have been subject to modification at the N and C terminals, allowing better understanding of lipase stability and the discovery of novel properties. A thermotolerant lipase has been isolated from Antarctic Pseudomonas sp. The purified Antarctic AMS3 lipase (native) was found to be stable across a broad range of temperatures and pH levels. The lipase has a partial Glutathione-S-transferase type C (GST-C) domain at the N-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Indeed, previous studies on Pseudomonas have reported it to be involved in food spoilage . Some studies showed that Pseudomonas not only produce some important enzymes, but also produce important biological metabolites that are used in industry . It is also worth noting that Pseudomonas can produce antibacterial substances and may play a role in improving the structure of microbial flora in Daqu or Baijiu production .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous studies on Pseudomonas have reported it to be involved in food spoilage . Some studies showed that Pseudomonas not only produce some important enzymes, but also produce important biological metabolites that are used in industry . It is also worth noting that Pseudomonas can produce antibacterial substances and may play a role in improving the structure of microbial flora in Daqu or Baijiu production .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies showed that Pseudomonas not only produce some important enzymes, but also produce important biological metabolites that are used in industry (35). It is also worth noting that Pseudomonas can produce antibacterial substances and may play a role in improving the structure of microbial flora in Daqu or Baijiu production (35). Yao et al reported Sphingobium for the first time in Baijiu, and this is the second report of it in Baijiu (6).…”
Section: Prokaryotic Microbial Diversitymentioning
confidence: 99%
“…In contrast with polar organic solvent, it has been reported that polar solvent can distort the water layer around the enzyme which make the enzyme less stable and lead to deactivation of the enzyme [16]. AMS8 lipase showed the maximum ester conversion was only at 36% in 1-butanol, a polar organic solvent which was 1-butanol.…”
Section: Effect Of Organic Solvents On the Esterification Reactionmentioning
confidence: 98%
“…As predicted, no FALDR and FACR activities were detected from the C- and N-terminal domains, respectively. It is unclear why, relative to wild-type maFACR, maFACR Nter has higher FALDR activity while maFACR Cter has lower FACR activity, but it is known that protein truncation can alter structural flexibility, substrate accessibility, and quaternary structure of enzymes, which could all affect the activity ( Gorfe et al, 2009 ; Yu et al, 2017 ; Latip et al, 2018 ). Nonetheless, these results strongly validate the hypothesis that the C-terminal domain is an FACR while the N-terminal domain functions as an FALDR.…”
Section: Resultsmentioning
confidence: 99%